Excellent ductility of an austenitic stainless steel at a high strength level achieved by a simple process - Wang, Yongqiang; Hu, Chaojun; Tian, Kai; Li, Na; Du, Juan; Shi, Xiaobin; Zheng, Chengsi (Materials & design, 2024)
[Display omitted] •A new austenitic stainless steel with high strength and excellent ductility was designed and manufactured by simple method.•The elongation of samples is up to 53.5–61 % under the yield and ultimate tensile strength level of 600–707 and 977–1020 MPa.•The product of strength and plasticity of this steel is the highest value comparing with other austenitic stainless steels.•There is the highest yield strength in this steel comparing with other austenitic stainless steels at the same elongation.•The excellent mechanical property of this steel is ascribed to a new multi-element collaborative strengthening mechanism. In the pursuit of simultaneously improving the yield strength and plasticity of austenitic stainless steel, a new austenitic stainless steel was fabricated by induction smelting using a pure N2 atmosphere, hot forging, cryogenic rolling, and annealing. The material was characterized by microstructures with 3–4 μm uniform finer grains, fine precipitates, high thermal stability austenite, and extensive high-angle grain boundaries. The elongation after fracture, yield strength, and ultimate tensile strength of the samples reached 53.5 %, 707 MPa, and 1020 MPa, respectively, as well as 61 %, 600 MPa, and 977 MPa, respectively, at the same time. Moreover, a high strain hardening rate was achieved in the new stainless steel. The appropriate uniform finer grains not only played a role in grain-refined strengthening but also provided intragranular spaces and sufficient mean free available paths for dislocation accumulation and movement. Precipitates, which were coherent or semi-coherent with the matrix, provided interfaces for dislocation accumulation and obstructions for dislocation movement. Extensive high-angle grain boundaries with appropriate finer grains served as another important factor for excellent ductility due to the inhabitation and resulting deviation of crack propagation. In addition, strain-induced mechanical twinning in the current austenitic stainless steel contributed to excellent ductility and high strength.